Training Method Transformation for Millennials Employees - Bujang, Nazarudin; Paramsivam, Mahaletchumi; Dasril, Yosza; Basar, Azizi (Research in Management of Technology and Business, 2021)
In the next decade, millennials employees will make up more than 50 percent of the workforce population. It is very essential for the employers to understand the characters of this generation and figure out ways on how to integrate, train and develop them which will enhance organization performance. Lack of loyalty and job-hopping are negative stereotypes surrounded millennials employees. This research is intended to determine the compatible training methods for millennials employees which will enable them to contribute effectively, integrate and add value to the organization. Quantitative survey and analysis was conducted involving 110 millennials employees who are working in Oil and Gas industry in the state of Johor. The most compatible and preferred training method was online training followed by micro learning and virtual training are the key findings. The outcome of this research is valuable for organization to plan their training programs for millennials employees and it is highly applicable currently as the whole world is coping with Covid-19 pandemic issues which restricted face to face and conventional training methods.